Effect of acid‐activation on CaO existential state and reactive properties of hot‐splashed steel slag in cement‐based materials. (14th March 2022) - Zhou, Yangmei; Ji, Yongsheng; Zhang, Zhongzhe; Ma, Zhanguo; Gao, Furong; Xue, Qi; Xu, Zhishan
Abstract: The over‐burnt free‐CaO(f‐CaO) existential state in hot‐splashed steel slag is understood by observing the microstructure of steel slag section and analyzing the minerals in the steel slag (SS). In the investigation, a new method of using hydrochloric acid as the solvent to modify the steel slag powder (SSP) is put forward. The effects of hydrochloric acid pretreatment on the surface morphology of SS and the hydration activity and soundness of SSP blended cement are investigated. Furthermore, the failure mechanism of steel slag cement‐based materials and the hydration mechanism of acid‐activated steel slag (ASS) are discussed in detail. The research indicated that the optimum dosage of modified SSP is 20 wt%. At this dosage, the 7‐ and 28‐day compressive strength of paste is nearly increased 15% compared with the untreated steel slag cement‐based mortar specimens. Moreover, the acid activated SS‐blended cement pastes show much better soundness performances after autoclaved curing tests when compared with corresponding pastes with SS without treatment. It provides a promising approach for efficient and safe utilization of SS as supplementary cementitious material.